Tax Avoidance Of Mining Industry Registered On Indonesia Stock Excgange Period 2020-2023 - Martini, Martini; Rismawandi, Rismawandi (STMIK Widya Cipta Dharma, 2025)
Tax revenue is one of the most significant sources of government income which will then be used in development aimed at the prosperity of the people. However, in practice, not all taxpayers (WP) are willing to pay taxes to the state. Various strategies can be carried out by WP in order to pay as little tax as possible which then carry out tax avoidance either legally or illegally. This study aims to obtain evidence regarding the effect of transfer pricing, profitability, and debt covenants on tax avoidance. The data in this study use secondary data in the form of financial reports through data collection obtained from the mining industry on the Indonesia Stock Exchange in 2020-2023. This study is a type of quantitative research that analyzes data to test hypotheses. The sample used consisted of 58 companies, with data processing using the SPSS version 23.0 program. The sampling technique used was purposive sampling, while data analysis was carried out through multiple linear regression. The results of the study showed that profitability had a negative and significant effect on tax avoidance, while transfer pricing and debt covenants did not have a significant effect on tax avoidance.